(untitled) (مجلة المنصور, 2023)
The research aims the behavior of power spectral density function for Gaussian Seasonal Autoregressive Model from order (2), by doing an spectral density function of different sample size for different Seasonal length and of different frequencies. Among the main conclusion is that PSD Values decrease gradually when the sample size, season length and frequencies increase.